2015
DOI: 10.1016/j.bbr.2015.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory motor network connectivity is associated with motor sequence learning after subcortical stroke

Abstract: Following stroke, functional networks reorganize and the brain demonstrates widespread alterations in cortical activity. Implicit motor learning is preserved after stroke. However the manner in which brain reorganization occurs, and how it supports behaviour within the damaged brain remains unclear. In this functional magnetic resonance imaging (fMRI) study, we evaluated whole brain patterns of functional connectivity during the performance of an implicit tracking task at baseline and retention, following 5 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 47 publications
4
40
0
1
Order By: Relevance
“…Without providing exact lesion information (cortical/subcortical), a further study demonstrated improved sleep-dependent offline learning in stroke patients for explicit and implicit tasks compared to healthy subjects (Meehan et al, 2011;Wadden et al, 2015;Wadden et al, 2017).…”
Section: Stage Ii-contributions Of Stroke Studies To Knowledge Of Tmentioning
confidence: 92%
See 2 more Smart Citations
“…Without providing exact lesion information (cortical/subcortical), a further study demonstrated improved sleep-dependent offline learning in stroke patients for explicit and implicit tasks compared to healthy subjects (Meehan et al, 2011;Wadden et al, 2015;Wadden et al, 2017).…”
Section: Stage Ii-contributions Of Stroke Studies To Knowledge Of Tmentioning
confidence: 92%
“…Concerning the affected (contralesional) hand, the results are heterogeneous. Some studies conclude that motor sequence learning is preserved (Meehan et al, 2011;Shin et al, 2005;Wadden et al, 2015), while other studies find an impairment of motor sequence learning for the affected hand after stroke (Dirnberger et al, 2013;Exner et al, 2001;Fleming et al, 2018;Gomez Beldarrain, 1999;Gomez Beldarrain et al, 2002;Vakil et al, 2000;Wadden et al, 2017). All available examples of these studies investigated patients in the chronic phase of stroke.…”
Section: Contributions Of Stroke Studies To the Present Understandimentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated disruptions in resting-state functional connectivity involving regions of motor [139, 137, 140], sensory, attention, and language [141] early after stroke. These disruptions often relate to the extent of white matter damage [142, 143].…”
Section: Spontaneous Mechanisms Of Functional Recoverymentioning
confidence: 99%
“…Additional work is warranted to substantiate these findings. Other examples of potential stroke biomarkers include total infarct volume [195], white matter tract injury [2022, 138, 196], cortical activation [42, 52, 91, 175, 138, 197, 198] and connectivity [139, 137, 145, 147, 177, 138, 199], and genetic polymorphisms derived from simple blood tests [15, 16, 200]. These measures may serve an important role in guiding treatment, stratifying subjects in intervention studies, and ultimately predicting functional outcome and response to therapy.…”
Section: The Role Of Biomarkersmentioning
confidence: 99%